Feasibility of sodium bicarbonate ingestion in artistic swimming performances - Sprenger, H. M. L.; van Biljouw, T.; Bentley, D. J. (Nutrients, 2025)
Purpose: We evaluated the feasibility of individualized sodium bicarbonate (NaHCO3) supplementation and its physiological effects on simulated artistic swimming duet performance, including blood buffering responses, perceived exertion, gastrointestinal (GI) tolerance, and performance scores.